Note to the Spanish Pharmacopoeia, IX Edition: Magnesium carbonate - García Villanova, R.; Thomas, J.; Bosch, F. (Ars Pharmaceutica (Internet), 1966)
A tritimetry and complexometric technics of evaluation of magnesium carbonate has been revised. We recommended a complexometric technic, using EDTA and a Erio T as indicator, in order to include it in the new Spanish Pharmacopeia edition.